1998
DOI: 10.1021/bi9812423
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Dependent Acetyl Transfer Partial Reaction of the Acetyl-CoA Decarbonylase/Synthase Complex:  Kinetics and Mechanism

Abstract: Acetyl-CoA decarbonylase/synthase (ACDS) is a multienzyme complex that plays a central role in energy metabolism in Methanosarcina barkeri grown on acetate. The ACDS complex carries out an unusual reaction involving net cleavage of the acetyl C-C and thioester bonds of acetyl-CoA. The overall reaction is composed of several partial reactions, one of which involves catalysis of acetyl group transfer. To gain insight into the overall reaction, a study was carried out on the kinetics and mechanism of the acetyltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
81
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 16 publications
6
81
1
Order By: Relevance
“…Reactions were carried out in 12 ϫ 75-mm glass tubes at 25°C and were initiated by addition of a 10-l aliquot of sufficiently diluted protein to 110 l of an assay solution that contained all the above components at concentrations needed to give the final values indicated in a total reaction volume of 120 l. A series of reactions were carried out for each enzymatic rate determination and stopped at different time points (from 0 to 8 min) by addition of 120 l of 2 mM TiCl 3 in 0.5 M sodium citrate, pH 4.0, and the mixtures were frozen in liquid nitrogen prior to analysis by HPLC for the products CoA and S-acetyl-3Ј-dephospho-CoA. HPLC analyses and calculation of reaction rates were performed as described previously (3).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Reactions were carried out in 12 ϫ 75-mm glass tubes at 25°C and were initiated by addition of a 10-l aliquot of sufficiently diluted protein to 110 l of an assay solution that contained all the above components at concentrations needed to give the final values indicated in a total reaction volume of 120 l. A series of reactions were carried out for each enzymatic rate determination and stopped at different time points (from 0 to 8 min) by addition of 120 l of 2 mM TiCl 3 in 0.5 M sodium citrate, pH 4.0, and the mixtures were frozen in liquid nitrogen prior to analysis by HPLC for the products CoA and S-acetyl-3Ј-dephospho-CoA. HPLC analyses and calculation of reaction rates were performed as described previously (3).…”
Section: Methodsmentioning
confidence: 99%
“…One of these was the full-length 472-amino acid protein, CdhC, and the other was a 397-amino acid form truncated at the C terminus, CdhC*. CdhC* includes all major regions of conservation among ␤ subunit homologs and is about 30 amino acids smaller than the estimated size of the native protein isolated in truncated form following disruption of the ACDS complex by partial proteolysis (2,3). SDS-gel electrophoresis showed that similar amounts of CdhC and CdhC* were produced over time after induction of E. coli cultures grown under anaerobic conditions, as described under "Materials and Methods."…”
Section: Overexpression and Purification Of The Acds ␤ Subunit-mentioning
confidence: 99%
See 3 more Smart Citations